Serum, milk, and tissue monensin concentrations in cattle with adequate and potentially toxic dietary levels of monensin: pharmacokinetics and diagnostic interpretation. Issue 4 (14th January 2016) - Puschner, B.; Bautista, A. C.; McKemie, D. S.; Gallego, S. M.; Woods, L. W.; Moore, C. E.; Knych, H. K.
Abstract : Used in both beef cattle and dairy cows, monensin can provide many health benefits but can, when unintended overexposures occur, result in adverse effects. Information on serum and tissue concentrations following overexposure and/or overt toxicosis which may aid in diagnostics and clinical outcome is lacking. The aim of this study was to determine concentrations of monensin in biological specimens following oral exposure for 10 days to an approved dose (1 mg/kg) and a higher dose (5 mg/kg) of monensin given daily on a body weight basis to 10 dairy cows. No deaths were reported; cows receiving 5 mg/kg showed early signs of toxicosis including depression, decreased feed intake, and diarrhea after 4 days of exposure. Histopathological findings were minimal in most cows. Pharmacokinetic modeling of the detected serum concentrations for the 1 and 5 mg/kg dose groups determined the Cmax, Tmax, and t 1/2 λ to be 0.87 and 1.68 ng/mL, 2.0 and 1.0 h, and 1.76 and 2.32 days, respectively. Mixed regression models showed that the dose level and days since last dose were significantly associated with monensin concentrations in all four tissues, and with cardiac troponin levels. The high dose resulted in a significant elevation of monensin in tissues at approximately 4.7 times compared to the monensin concentrations in the tissues of animals from the low‐dose group. The cTnI concentrations in the high‐dose group were 2.1 times that of cTnI in the low‐dose group. Thus, the ability to diagnose monensin overexposure and/or toxicosis will improve from knowledge of biological monensin concentrations from this study.